The Accountability of the Perpetrator of a Crime Proven by Law and Convincingly Committing Fraud and Intentionally Forcing Sexual Intercourse with a Child (A Study of Decision Number: 50/Pid.Sus-Anak/2024/PN.Tjk) - Hamaminata, Gani; Prasetyawati, S. Endang; Aprinisa, Aprinisa (The Future of Education Journal, 2025)
With the rise in cases of sexual violence against children, including those involving perpetrators who are still children, it has been found that law enforcement against child perpetrators still faces challenges, including in implementing sanctions that provide a deterrent effect while fulfilling the principles of justice for victims. This research aims to examine the responsibility of perpetrators of criminal acts who are legally and convincingly proven to have committed deception to force sexual intercourse with a child, with a case study in Decision Number: 50/Pid.Sus-Anak/2024/PN.Tjk. This research is supported by an in-depth literature review regarding the meaning of children, criminal acts of sexual intercourse and regulations related to criminal acts of sexual intercourse with children. This research also examines the basis for the judge's consideration in deciding whether to punish a criminal who has been legally proven to have committed a deception to intentionally force sexual intercourse with a child in case decision Number: 50/Pid.sus¬Anak/2024/PN.Tjk. The research method used in this research is a normative and empirical juridical approach using secondary and primary data collected through literature and field studies. The results of the research showed that the perpetrators, who were still children, were sentenced to one year in prison at the Special Children's Development Institution and two months of work training. The Tanjungkarang District Court is advised to increase its capacity in handling cases of sexual violence against children through training and in-depth understanding of child protection issues, and the Bandar Lampung City Police are advised to create special training for investigators in handling sexual cases against children and tighten supervision. to the social environment.